Konsep Khidmah dalam Qs. Al-Kahfi [18]: 60-64 dan Relevansinya terhadap Santri Mandiri - Ihsanillah, Muhammad Mu'tamid; Badi'ah (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2024)
Khidmah (dedication) is the willingness of students to devote themselves to their kyai to strengthen the process of understanding religion (tafaqquh fi al-din) in the pesantren. However, in the view of the general public, khidmah is often perceived as 'exploitation' because it entails instructing students to work in pesantren institutions or businesses without adequate compensation commensurate with their efforts. The busy schedule involving religious studies, academic pursuits, and khidmah impacts the academic achievements of students. This situation sometimes leads students to complain and blame circumstances, resulting in a negative perception of khidmah. This research aims to analyze the concept of khidmah from the perspective of the Qur'an, particularly QS. Al-Kahfi [18]: 60-64, to gain a correct understanding of khidmah. Furthermore, this study applies the interpretation of these verses to self-reliant students of Pesantren Sunan Pandanaran. The research adopts a descriptive-qualitative method with a literature review approach. The findings reveal the concept of khidmah in QS. Al-Kahfi emphasizes the dedication and loyalty of a student in serving their teacher with sincerity and humility to acquire knowledge and the pleasure of Allah SWT, thus obtaining blessings in life. The concept of khidmah in the stories of Prophet Musa, Prophet Khidir, and Yusa’ bin Nun is highly relevant to the khidmah practiced by self-reliant students of Pondok Pesantren Sunan Pandanaran. Through khidmah in the Islamic boarding school, self-reliant students can equip themselves for future service in society, thereby realizing the concept of Khadim al-Ilm - Khadim al-Ummah.